2014
DOI: 10.1590/0103-6440201302414
|View full text |Cite
|
Sign up to set email alerts
|

Manual and Rotary Instrumentation Ability to Reduce Enterococcus faecalis Associated with Photodynamic Therapy in Deciduous Molars

Abstract: This aim of this study was to assess the ability of manual or rotary instrumentation associated with photodynamic therapy (PDT) to reduce Enterococcus faecalis using three combinations of light/photosensitizers: toluidine blue O/laser, fuchsin/halogen light and fuchsin/LED. Twenty deciduous molars were selected and contaminated with Enterococcus faecalis (McFarland 0.5 scale). Working length determination was performed by visual method. The teeth were randomly divided into two groups: G1 (n=10): manual instrum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 22 publications
1
17
0
1
Order By: Relevance
“…In a previous study [10], the authors used the small 21:06 CRT file of 21 mm in length, of the WaveOne system and it was observed that it was effective for disinfecting and modeling the root systems of primary molars [7,9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a previous study [10], the authors used the small 21:06 CRT file of 21 mm in length, of the WaveOne system and it was observed that it was effective for disinfecting and modeling the root systems of primary molars [7,9].…”
Section: Discussionmentioning
confidence: 99%
“…The WaveOne system allows greater flow of irrigating solution by removing smaller amounts of dentin from the channel walls [6], thus reducing the extrusion of debris and reducing the risk of damaging or frustrating the instrument in irregular channels as presented the primary teeth [5][6][7]. This method has also been shown to be more effective in disinfecting the radial channels of deciduous molars [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,15,16 Comparing rotary instruments with manual instruments in terms of intracavitary microorganism elimination demonstrated that both systems significantly reduced the number of microorganisms and that there was no statistical difference between them. [17][18][19] Conventional stainless steel files were reported to remove more dentin tissue, especially in the coronal region. Although the difference between them and rotary instruments was not significant, stainless steel files were indicated to provide more efficient cleaning.…”
Section: Rotary Instruments Used In Root Canal Therapiesmentioning
confidence: 99%
“…Many authors demonstrated the positive effect of PDT on E. faecalis reduction on extracted human teeth when it was accompanied by various protocols [25][26][27][28][29]. Some authors demonstrated that the effect of PDT in combination with various antimicrobial irrigants (NaOCl and EDTA) was more pronounced against E. faecalis, while the effect of irrigants alone was greater against Streptococcus mutans [25].…”
Section: Discussionmentioning
confidence: 99%